(untitled) (Boletín Epidemiológico Semanal, 2025)
Introduction: To describe the prevalence of the main modifiable risk factors in adults with chronic diseases in Spain. Method: Data come from 67,451 individuals aged ≥15 years participating in the National Health Survey 2017 and European Health Surveys 2014 and 2020. Prevalences of tobacco use, alcohol consumption, fruit and vegetable consumption, and leisure-time physical activity were estimated in individuals with a history of myocardial infarction (n=1,530), stroke (n=1,382), diabetes (n=6,309), chronic obstructive pulmonary disease (COPD, n=2,831), asthma (n=3,078), and cancer (n=3,086). Results: Current tobacco use ranged from 22.5% in people with COPD to 13.4% with a history of heart attack. The highest prevalence of high-risk drinking was observed in the population with asthma and COPD (11.6% and 11.5%), and the lowest in people with stroke (5.9%). Consumption <3 times/day of fruit and/or vegetables ranged from 61.8% in those with asthma to 49.8% in people with cancer. Finally, the highest prevalence of leisure-time sedentary lifestyle was observed in people with a history of stroke (55.8%), and the lowest in individuals with asthma (41.8%). Conclusions: The study reveals a high prevalence of risk factors in individuals with chronic diseases, with a predominance of sedentary lifestyles and insufficient fruit and vegetable consumption. In the framework of secondary and tertiary prevention, these results underline the need to implement intervention strategies that effectively address these behaviours to improve the control of these diseases.